A ação espasmolítica do óleo essencial de Xylopia frutescens Aubl. envolve a redução dos níveis citosólicos de cálcio em íleo de cobaia - Souza, Iara Leão Luna de (2014)
Xylopia frutescens Aubl. species, popularly known as “embira”, “semente-de-embira” and “embira-vermelha”, is used in folk medicine as antidiarrhoeal. From leaves of these species was extract the essential oil (XF-OE), that in previous studies, showed spasmolytic activity on phasic contractions induced by CCh or histamine on guinea pig ileum. Considering this premise, the aim of this study was to characterize the mechanism of spasmoliytic action of XF-OE on intestinal smooth muscle. For this, were used functional and cellular methodologies. XF-OE inhibited cumulative concentration-response curves to histamine, and these were shifted to the right, in a non-parallel manner, with Emax reduction, discarding thus a competitive type antagonism and relaxed the guinea pig ileum contracted by KCl (40 mM) or histamine (10-6 M). How the relaxant potency of the essential oil was smaller in organ pre-contracted by KCl, it was hypothesized that XF-OE would be acting as a K+ channels positive modulator. In presence of CsCl (5 mM), a non-selective blocker of these channels, the relaxant potency of XF-OE was not altered, showed a non-participation of K+ channels on the essential oil spasmolytic effect. Thus, we decided to check whether the essential oil would prevent calcium influx through CaV, for this were obtained cumulative concentration-response curves to CaCl2 in depolarizing medium (70 mM KCl) nominally without Ca2+ in absence (control) and presence of different concentrations of XF-OE. The essential oil shifted to the right CaCl2 control curves, with reduction of its Emax, in addition to relaxed the ileum pre-contracted by S-(-)-Bay K8644 (3 x 10-7 M), a CaV1 selective agonist, demonstrating that the essential oil inhibited Ca2+ influx through CaV1. As the Ca2+ mobilization mechanisms into circular and longitudinal muscle layers are differentiated, it was hypothesized that XF-OE would preventing Ca2+ mobilization from intracellular stores in order to promote its spasmolytic effect. To test this hypothesis, in experiments with ileum circular layer, the essential oil antagonized phasic contractions induced by histamine (10-5 M), negatively modulates the Ca2+ release to exert their spasmolytic effect. In cellular experiments, the viability of longitudinal layer myocytes from guinea pig ileum was not altered in XF-OE (81 μg/mL) presence and the fluorescence intensity in these intestinal myocytes stimulated by histamine was reduced by the essential oil, indicating a [Ca2+]c reduction. Thus, the XF-OE spasmolytic action mechanism on guinea pig ileum involves blocking the Ca2+ influx, by CaV1, in addition to negative modulation of Ca2+ release mechanisms from intracellular stores, that lead to reduction of this ion cytosolic levels and consequently muscle relaxation.